Działalność Komisji Badań nad Antykiem Chrześcijańskim TN KUL w roku akademickim 2024/2025 - Głowa, Anna (Vox Patrum, 2025)
Activity of the Committee for Research on the Christian Antiquity of the Learned Society KUL in the Academic Year 2024/2025